«The Kolchak regime was based on the main ideological component — antiBolshevism, which in those conditions did not need additional clarification of the political program ...» - A. S. Puchenkov (Омский научный вестник: Серия "Общество. История. Современность")
Alexander Sergeevich Puchenkov is St. Petersburg historian, doctor of historical sciences, well-known expert on the Civil War in Southern Russia. This interview was given to A. V. Sushko, the deputy chief editor of the journal Omsk Scientific Bulletin. Series Society. History. Modernity as a result of his participation in the II All-Russian Scientific and Practical Conference «Civil War in Eastern Russia: The View through the Documentary Heritage», held in Omsk, October 2017. It is dedicated to the personality and historical memory of Admiral A. V. Kolchak — the leader of White movement in Russia. The interview was finally edited by A.S. Puchenkov in St. Petersburg in September 2018